Harnessing Dark Energy in Five-dimensional Brans-Dicke Universe - Singh, Kangujam Priyokumar; Singh, Koijam Manihar (Communications in Physics, 2021)
In trying to explain the present accelerated expansion of the universe in the light of a five-dimensional Brans-Dicke theory, it is found that the fifth dimension itself here acts as a source of dark energy. It may be taken as a curvature-induced form of dark energy, in one case of which it behaves similar to that form of dark energy arising out of the cosmological constant which is the most commonly accepted form of dark energy. It is also found that this new type of dark energy is free from big rip singularity and may be taken as a viable form of dark energy which can explain some of physical mysteries of the universe